Метод синтеза единой структурной составляющей реляционной модели данных - Левыкин, В. М.; Филатов, В. А.; Черненко, Н. И. (My University, 2011)
Розглянуто метод структурної інтеграції схем реляційних баз даних, що спроектовані та функціонують незалежно. Проведено дослідження реляційної моделі, можливі варіанти інтеграції кількох схем реляційних баз даних, запропоновано метод синтезу єдиної структурної складової реляційної моделі даних. A method of structural integration of the schemes of the projected and functioning data bases of various relational models into a single one is suggested. A relational model and the possible variants of the integration of several schemes of relational databases are investigated. A method of the synthesis of a single structural component of the relational data model is described.
Keywords: информационные системы; реляционные базы данных; структурная интеграция схем реляционных баз данных